PEDAGOGICAL STRATEGIES FOR ENHANCING STUDENTS’ ARTISTIC COMPETENCIES THROUGH INTERACTIVE VISUAL ARTS LESSONS - Gadoyev Ibrohim Niyozovich (НАУЧНЫЕ ИССЛЕДОВАНИЯ И ИННОВАЦИИ, 2025)
Abstract: This article explores pedagogical strategies for enhancing students’ artistic competencies in visual arts lessons. The study focuses on interactive methods, problem-solving tasks, and practical exercises that develop students’ creativity, visual literacy, and independent artistic skills. The article emphasizes how incorporating innovative teaching approaches can stimulate students’ engagement, critical thinking, and aesthetic development.